2021
DOI: 10.9734/jpri/2021/v33i30b31649
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of New RP-HPLC Method for the Estimation of Antidiabetic Drugs Metformin Hydrochloride and Gemigliptin in Combined Pharmaceutical Dosage Form

Abstract: Metformin Hydrochloride and Gemigliptin is combination of Antidiabetic drug in tablet Zemimet SR ® Tablet (25/500 mg), a member Antidiabetic drug, is a recent drug developed by LG Life sciences for the treatment of Type 2 diabetes. A new sensitive and rapid HPLC method was developed for the determination of Metformin Hydrochloride and Gemigliptin in pharmaceutical dosage forms; it was validated according to International Conference on Harmonization and Food and Drug Administration guidelines. The analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A simple reverse phase HPLC method was developed to determine Metformin 22 and Saxagliptin present in pharmaceutical dosage forms of 500 mg and 5mg. Column 9 used Hypersil Silica (250 x 4.6 mm, packed with 5μm) in an isocratic mode with mobile phase Buffer: Acetonitrile (55:45) was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple reverse phase HPLC method was developed to determine Metformin 22 and Saxagliptin present in pharmaceutical dosage forms of 500 mg and 5mg. Column 9 used Hypersil Silica (250 x 4.6 mm, packed with 5μm) in an isocratic mode with mobile phase Buffer: Acetonitrile (55:45) was used.…”
Section: Methodsmentioning
confidence: 99%
“…From the filtered solution, 1ml was pipetted out into a 10 ml volumetric flask and made upto 10ml with diluents 13 . Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 .…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation